Perancangan Balanced Scorecard sebagai Pengukuran Kinerja pada PT Asuransi MSIG Indonesia - ramadhani, ramadhani; trisyulianti, erlin (Jurnal Manajemen dan Organisasi, 2016)
PT MSIG move in the field of damage insurance and it is trying to design a system of measurement of performance comprehensive. The purpose of this research is to identify indicators used in employee performance measurement in PT MSIG, formulating concept of balanced score card (BSC) system that is suitable to the company performance measurement, and to develop BSC simulation which is in accordance to company vision, mission, and strategy. The results of this research indicate that financial performance measurements are classified as good. In BSC formulation, it is showed that customer perspective is the most important perspective in the performance evaluation with the score of 29%. In BSC simulation, it is showed that performance measurement is classified as good based on csale of 75%. Data used in this research was primary and secondary data. While data analysis method used was BSC analysis, Analytical Hierarcy Process (AHP) analysis, and Strengths, Weakneass, Opportunities, and Threaths (SWOT) analysis.